Hydrogen evolution cathode and preparation method and application thereof

By coating a NiMoN compound onto a cathode substrate and then covering it with a carbon layer, the problems of environmental pollution and high cost in the preparation of nickel-molybdenum-based hydrogen evolution cathodes have been solved, resulting in a hydrogen evolution cathode with high catalytic activity and stability, suitable for hydrogen production by water electrolysis.

CN120818831APending Publication Date: 2025-10-21QINGDAO GREEN DEV RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410438960.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-12
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

The existing preparation methods of nickel-molybdenum-based hydrogen evolution cathodes have problems of serious environmental pollution and high cost, and are difficult to replace precious metal catalysts.

Method used

An active material precursor, binder, and solvent are mixed to form a slurry, which is then coated onto a cathode substrate and sintered in a reducing atmosphere to form a NiMoN compound and a carbon coating, thereby improving the bonding force between the active material and the substrate and the catalytic activity.

Benefits of technology

The prepared hydrogen evolution cathode has high catalytic activity, low hydrogen evolution overpotential and high stability. It is environmentally friendly and low in cost, and is suitable for hydrogen production by water electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818831A_ABST
    Figure CN120818831A_ABST
Patent Text Reader

Abstract

The invention provides a hydrogen evolution cathode and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing an active material precursor, a binder and a solvent to obtain slurry; and (2) coating the slurry on the surface of a cathode substrate, and sintering in a reducing atmosphere to obtain the hydrogen evolution cathode, wherein the active material precursor comprises a Ni source and a Mo source; the binder comprises a C element and an N element. According to the preparation method of the hydrogen evolution cathode, the binding force of the active material and the substrate can be improved, the hydrogen evolution catalytic activity and stability of the hydrogen evolution cathode are improved, environmental pollution is small, expensive equipment and raw materials are not needed, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water, and relates to a hydrogen evolution cathode and a preparation method and application thereof. Background Art

[0002] Hydrogen energy is a plentiful, green, low-carbon, and widely applicable secondary energy source. It can facilitate the large-scale consumption of renewable energy, achieve large-scale peak-shaving of power grids, and provide cross-seasonal and cross-regional energy storage, accelerating the decarbonization of industries, construction, transportation, and other sectors. It has been hailed as the "ultimate energy source" of the 21st century. Hydrogen energy is gradually becoming a key vehicle for global energy transformation and development. It is also a crucial path to promoting a revolution in energy production and consumption, building a clean, low-carbon, safe, and efficient energy system, and achieving the goals of "carbon peak and carbon neutrality." Hydrogen can be produced by water electrolysis. During this process, a hydrogen evolution reaction occurs at the cathode, involving electron transfer and proton coupling. The kinetic hysteresis of the hydrogen evolution reaction is a bottleneck in the water splitting reaction. Therefore, developing highly catalytically active hydrogen evolution cathodes and reducing the hydrogen evolution overpotential can help improve energy conversion efficiency and reduce the energy consumption of hydrogen production by water electrolysis.

[0003] Cathodes with precious metal catalysts such as Pt, Ru, or Pd have low overpotentials and are widely used in hydrogen evolution cathodes. However, due to limited natural resources, the price of precious metal catalysts is too high. Therefore, it is necessary to find cheap and efficient non-precious metal catalysts. If the development of non-precious metal catalyst electrodes is to achieve the effect of precious metal catalysts, it is necessary to pay attention to the following points: first, to increase the specific surface area of ​​the electrode material and increase the contact area between the electrolyte and the electrode; second, to optimize the electrode composition and improve the activity and stability of the electrode through alloying, creating point defects, etc.; third, to improve the electrode's antioxidant capacity and use a protective layer to buffer the damage to the electrode catalyst layer structure caused by the electrochemical reaction, thereby increasing the electrode life.

[0004] Nickel-molybdenum-based compounds serve as catalysts, and the resulting nickel-molybdenum-based hydrogen evolution cathodes exhibit excellent electrochemical performance, making them a preferred alternative to precious metal catalysts. For example, Wang Jin et al. (Preparation of Nickel-Based Ni-Mo Alloy Electrodes and Study of Their Electrocatalytic Hydrogen Evolution Performance [D]. Chongqing University, 2014) reported a method for preparing a Ni-Mo-P / Ni electrode. The electrode, prepared using electrodeposition and magnetron sputtering, exhibited a positive shift in hydrogen evolution potential by 270 mV, reduced resistance, and improved stability. CN114250485A discloses a nickel-molybdenum-iron hydrogen evolution electrode with an ordered porous structure, its preparation method, and its application. After attaching a microsphere template to a nickel-based substrate, NiMo is electrodeposited in a mixed solution of a high-concentration nickel source, molybdenum source, sodium citrate, sodium chloride, and urea. The template is then removed to produce an isoporous nickel-molybdenum foam, which is then impregnated with Fe to produce a NiMoFe hydrogen evolution cathode. This hydrogen evolution cathode effectively reduces the cell voltage of the electrolytic cell. However, the preparation methods of the aforementioned schemes each present different challenges. For example, the electroplating method causes serious environmental pollution and is difficult to be approved for production; the equipment and raw material costs of the magnetron sputtering method are too high.

[0005] Therefore, there is an urgent need to provide a method for preparing a nickel-molybdenum-based hydrogen evolution cathode that has little pollution to the environment and is low in cost. Summary of the Invention

[0006] In response to the shortcomings of the prior art, the present invention aims to provide a hydrogen evolution cathode, its preparation method, and its application. The present invention's preparation method for a hydrogen evolution cathode can improve the bonding strength between the active material and the substrate, enhance the cathode's hydrogen evolution catalytic activity and stability, cause minimal environmental pollution, and eliminate the need for expensive equipment and raw materials, resulting in a low cost.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a hydrogen evolution cathode, the preparation method comprising:

[0009] (1) mixing an active material precursor, a binder, and a solvent to obtain a slurry;

[0010] (2) coating the slurry on the surface of a cathode substrate, and then sintering the slurry under a reducing atmosphere to obtain the hydrogen evolution cathode;

[0011] The active material precursor includes a Ni source and a Mo source; and the binder includes C and N elements.

[0012] The present invention provides a method for preparing a hydrogen evolution cathode, which has the following advantages:

[0013] (1) The present invention uses a binder to uniformly form an active material precursor into a slurry and apply it to the cathode substrate, which is then sintered and solidified to obtain a hydrogen evolution cathode. This method significantly improves the bonding strength between the active material and the substrate; the binder can play a bonding role during the slurrying process, allowing the slurry to be evenly coated on the cathode substrate;

[0014] (2) The active material precursor of the present invention includes a Ni source and a Mo source. The Ni source and the Mo source react during the sintering process to form a Ni-Mo compound with high hydrogen evolution catalytic activity and firmly adhere to the substrate. At the same time, the N (nitrogen) element in the binder can serve as a nitrogen source. During the sintering process, part of the N element is doped into the Ni-Mo compound to form a NiMoN compound, further enhancing the hydrogen evolution catalytic activity.

[0015] (3) The binder of the present invention not only plays the role of bonding and serving as a nitrogen source, but the C (carbon) element in the binder can also serve as a carbon source. During the sintering process, part of the binder is carbonized, and the carbonized amorphous carbon is attached to the surface of the NiMoN compound to form a carbon coating layer. The carbon coating layer and the NiMoN compound form a shell-core structure; the carbon coating layer acts as a protective layer to prevent the NiMoN high catalytic activity compound from being oxidized, thereby improving stability;

[0016] (5) The present invention performs sintering under a reducing atmosphere, which can eliminate oxygen in the sintering environment and oxygen elements in the Ni-Mo compound, making the generated NiMoN compound purer;

[0017] (6) The method of the present invention has little pollution to the environment and does not require expensive equipment and raw materials, so the cost is low.

[0018] Preferably, the Ni source includes at least one of a single Ni substance, a Ni-containing alloy, and a Ni-containing compound.

[0019] Preferably, the Ni-containing compound comprises a Ni salt, and the Ni salt comprises NiMoO 4 .

[0020] Preferably, the Mo source includes at least one of a simple Mo substance, a Mo-containing alloy, and a Mo-containing compound.

[0021] Preferably, the Mo-containing compound comprises a Mo salt, and the Mo salt comprises NiMoO 4 .

[0022] Preferably, the Ni source is NiMoO4, and the Mo source is NiMoO4. In this case, NiMoO4 serves as both a Ni source and a Mo source.

[0023] The present invention does not limit the source of NiMoO4. Commercially available products can be directly purchased, or Ni-containing compounds and Mo-containing compounds can be synthesized by chemical or physical reaction in proportion through hydrothermal method, pyrolysis method or ball milling method.

[0024] Preferably, in the active material precursor, the molar ratio of Ni element to Mo element is 1:(0.1~3), for example, it can be 1:0.1, 1:0.2, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3 or 1:3.5, etc., but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0025] Preferably, the binder includes a first binder, and the first binder includes any one of polyvinyl pyrrolidone, nitrogen-containing resin, or LA type water-based binder, or a combination of at least two thereof.

[0026] Preferably, the binder further includes a second binder, and the second binder includes any one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, polymethacrylate or polyvinylidene fluoride, or a combination of at least two thereof.

[0027] Preferably, the mass ratio of the binder to the active material precursor is 1:(4-100), for example, it can be 1:4, 1:5, 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90 or 1:100, etc., but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0028] In the present invention, if the mass ratio of the binder to the active material precursor is too low, the slurry viscosity will be low, the active load layer will easily crack during the drying process, and powder will occur during the electrolysis process, thereby affecting the electrode catalytic performance; if the mass ratio of the binder to the active material precursor is too high, the unit loading of the active material will be reduced, and the electrode catalytic performance will be reduced.

[0029] Preferably, the solvent includes any one of water, ethanol, acetone or N-methylpyrrolidone, or a combination of at least two thereof.

[0030] Preferably, when the solvent is water, the solvent is heated during the mixing process with the binder, and the heating temperature is 40 to 95°C, for example, 40°C, 50°C, 50°C or 80°C.

[0031] Preferably, the mixing in step (1) is a step-by-step mixing, and the step-by-step mixing includes the following steps: firstly mixing the binder and the solvent to obtain a binder glue solution, and then mixing the binder glue solution with the active material precursor.

[0032] Preferably, the mass ratio of the binder to the solvent in the binder glue is 1:(1-100), for example, it can be 1:1, 1:5, 1:10, 1:20, 1:30, 1:50, 1:60, 1:80 or 1:100, etc., but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0033] Preferably, the viscosity of the slurry is 800-10000 mPa·s, for example, it can be 800 mPa·s, 900 mPa·s, 1000 mPa·s, 1100 mPa·s, 1200 mPa·s, 1500 mPa·s, 2000 mPa·s, 3500 mPa·s, 5000 mPa·s, 6000 mPa·s, 8000 mPa·s, 8500 mPa·s, 8900 mPa·s, 9000 mPa·s or 10000 mPa·s, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In the present invention, if the viscosity of the slurry is too low, it will be difficult for the slurry to be loaded on the base material as designed, resulting in low quality of the active material and affecting the catalytic performance; if the viscosity of the slurry is too high, it will challenge the coating process, resulting in uneven coating and affecting the consistency of the electrode.

[0035] Preferably, the cathode substrate comprises a nickel-based substrate, and the nickel-based substrate comprises any one or a combination of at least two of nickel foam, nickel-containing alloy foam, nickel mesh or nickel-containing alloy mesh.

[0036] Preferably, the coating method includes any one of scraping, brushing, spraying or slurrying, or a combination of at least two of them.

[0037] Preferably, the total coating amount of the active material precursor and the binder is 10 to 500 mg / cm 2 , for example, it can be 10 mg / cm 2 , 20mg / cm 2 , 50mg / cm 2 、80mg / cm 2 、100mg / cm 2 , 200mg / cm 2 、300mg / cm 2 , 400mg / cm 2 or 450mg / cm 2 etc., but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the coated product is pre-dried before the sintering.

[0039] Preferably, the pre-drying temperature is 40-95°C, for example, it can be 40°C, 60°C, 80°C or 90°C, and the pre-drying time is 3-30min, for example, it can be 3min, 5min, 8min, 10min, 15min, 20min, 25min or 30min, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0040] Preferably, the sintering heating rate is 5 to 20°C / min, for example, it can be 5°C / min, 7°C / min, 10°C / min, 12°C / min, 15°C / min or 18°C / min, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0041] Preferably, the sintering temperature is 300-1000°C, for example, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C or 900°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] Preferably, the sintering time is 20 to 1000 min, for example, it can be 20 min, 50 min, 80 min, 100 min, 150 min, 200 min, 300 min, 500 min, 600 min, 700 min, 800 min, 850 min or 900 min, but is not limited to the listed values. Other values ​​not listed within this numerical range are also applicable.

[0043] Preferably, the reducing gas in the reducing atmosphere includes ammonia.

[0044] In the present invention, ammonia can be used not only as a reducing agent but also as a nitrogen source, thereby further increasing the doping amount of the N element in the Ni-Mo compound, which is beneficial to further improving the catalytic activity of hydrogen evolution.

[0045] Preferably, the rate of ammonia gas introduced is 10 mL / min to 50 L / min, for example, 10 mL / min, 20 mL / min, 50 mL / min, 80 mL / min, 100 mL / min, 200 mL / min, 500 mL / min, 800 mL / min, 1 L / min, 2 L / min, 5 L / min, 10 L / min, 20 L / min, 40 L / min or 50 L / min, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0046] As a preferred technical solution of the present invention, the preparation method specifically comprises the following steps:

[0047] (I) mixing a binder and a portion of a solvent to obtain a binder paste, and then mixing the binder paste, an active material precursor, and the remaining portion of the solvent to obtain a slurry;

[0048] The active material precursor includes a Ni source and a Mo source; in the active material precursor, the molar ratio of Ni element to Mo element is 1:(0.1-3); the binder includes C element and N element; the mass ratio of the binder to the active material precursor is 1:(4-100); the mass ratio of the binder to the solvent in the binder glue is 1:(1-100); the viscosity of the slurry is 800-10000 mPa·s;

[0049] (II) coating the slurry on the surface of a cathode substrate, and then pre-drying the slurry at 40-95° C. for 3-30 minutes, then placing the pre-dried product in a first atmosphere, heating it to 300-1000° C. at a heating rate of 5-20° C. / min, introducing a reducing gas, and sintering it in the reducing atmosphere for 20-1000 minutes. After sintering, placing it in a second atmosphere for cooling to obtain the hydrogen evolution cathode;

[0050] The total coating amount of the active material precursor and the binder is 10 to 500 mg / cm 2 ; The reducing gas in the reducing atmosphere includes ammonia, and the amount of ammonia introduced is 10 mL / min to 50 L / min; the first atmosphere and the second atmosphere are both protective atmospheres, and the gases in the first atmosphere and the second atmosphere independently include argon and / or nitrogen, and the gas flow rates in the first atmosphere and the second atmosphere are independently 10 mL / min to 50 L / min (for example, it can be 10 mL / min, 20 mL / min, 50 mL / min, 80 mL / min, 100 mL / min, 200 mL / min, 500 mL / min, 800 mL / min, 1 L / min, 2 L / min, 5 L / min, 10 L / min, 20 L / min, 40 L / min or 50 L / min, etc.).

[0051] In a second aspect, the present invention provides a hydrogen evolution cathode, which is prepared by the preparation method described in the first aspect;

[0052] The hydrogen evolution cathode comprises a cathode substrate and an active material layer arranged on the surface of the cathode substrate; the active material in the active material layer comprises a NiMoN compound and a C coating layer coated on the surface of the NiMoN compound.

[0053] The nickel-molybdenum-based hydrogen evolution cathode prepared by the preparation method of the present invention has high catalytic activity, high porosity, low hydrogen evolution overpotential and high stability. The active material in the hydrogen evolution cathode has a core-shell structure.

[0054] In a third aspect, the present invention provides an application of the hydrogen evolution cathode described in the second aspect, wherein the hydrogen evolution cathode is applied in the field of hydrogen production by electrolysis of water.

[0055] The numerical range described in the present invention includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] The present invention provides a method for preparing a hydrogen evolution cathode, which has the following advantages:

[0058] (1) The present invention uses a binder to uniformly form an active material precursor into a slurry and apply it to the cathode substrate, which is then sintered and solidified to obtain a hydrogen evolution cathode. This method significantly improves the bonding strength between the active material and the substrate; the binder can play a bonding role during the slurrying process, allowing the slurry to be evenly coated on the cathode substrate;

[0059] (2) The active material precursor of the present invention includes a Ni source and a Mo source. The Ni source and the Mo source react during the sintering process to form a Ni-Mo compound with high hydrogen evolution catalytic activity and firmly adhere to the substrate. At the same time, the N (nitrogen) element in the binder can serve as a nitrogen source. During the sintering process, part of the N element is doped into the Ni-Mo compound to form a NiMoN compound, further enhancing the hydrogen evolution catalytic activity.

[0060] (3) The binder of the present invention not only plays the role of bonding and serving as a nitrogen source, but the C (carbon) element in the binder can also serve as a carbon source. During the sintering process, part of the binder is carbonized, and the carbonized amorphous carbon is attached to the surface of the NiMoN compound to form a carbon coating layer. The carbon coating layer and the NiMoN compound form a shell-core structure; the carbon coating layer acts as a protective layer to prevent the NiMoN high catalytic activity compound from being oxidized, thereby improving stability;

[0061] (5) The present invention performs sintering under a reducing atmosphere, which can eliminate oxygen in the sintering environment and oxygen elements in the Ni-Mo compound, making the generated NiMoN compound purer;

[0062] (6) The method of the present invention has little pollution to the environment and does not require expensive equipment and raw materials, so the cost is low.

[0063] The hydrogen evolution cathode prepared by the preparation method of the present invention has high catalytic activity, high porosity, low hydrogen evolution overpotential and high stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is the potential step curve of the hydrogen evolution cathode provided in Example 1 of the present invention at different current densities.

[0065] Figure 2 This is the XRD pattern of the hydrogen evolution cathode provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0067] Example 1

[0068] This embodiment provides a method for preparing a hydrogen evolution cathode, the method comprising:

[0069] (1) Prepare the materials according to the mass ratio of Ni powder: Mo powder: polyvinyl pyrrolidone: carboxymethyl cellulose: styrene-butadiene rubber (50% emulsion): deionized water = 50:45:1.5:1.5:2:120;

[0070] (2) Ni powder and Mo powder were placed in a ball mill and milled at a speed of 240 rpm for 2 h to obtain an active material precursor;

[0071] (3) Polyvinyl pyrrolidone and carboxymethyl cellulose are placed in half of the deionized water in the preparation, heated to 60°C, and stirred to form a binder glue;

[0072] (4) Mixing the active material precursor and the binder glue and stirring them thoroughly;

[0073] (5) Styrene-butadiene rubber (50% emulsion) was placed in the stirred mixed solution, and the remaining half of the deionized water in the preparation was added and stirred thoroughly to obtain a slurry with a viscosity of 2000 mPa·s;

[0074] (6) The slurry was evenly coated on a 10 cm*10 cm nickel foam with a scraper to control the thickness; then it was pre-dried at 80°C for 5 min. After pre-drying, the coating load of the material on the nickel foam was weighed to be 45 mg / cm 2 ;

[0075] (7) The pre-dried nickel foam loaded with the slurry was placed in a reactor and vacuumed. Argon gas was then introduced at a flow rate of 50 mL / min. The temperature was then raised at a heating rate of 8°C / min. When the temperature reached 460°C, ammonia gas was introduced at a flow rate of 30 mL / min. The product was sintered in an ammonia atmosphere for 90 min. After sintering, argon gas was introduced at a flow rate of 50 mL / min.

[0076] (8) After the temperature in the furnace drops to room temperature, a hydrogen evolution cathode is obtained.

[0077] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 6600-6800 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis. In addition, the active material and the substrate in the hydrogen evolution cathode of this embodiment have strong bonding strength, are not easy to fall off, and have good stability.

[0078] Add a saturated calomel reference electrode and a titanium ruthenium counter electrode to form a three-electrode system with the hydrogen evolution cathode of this embodiment. The three-electrode test results are as follows: Figure 1 As shown, at 6000A / m 2 At the current density, the potential is -1.586 V (vs. SCE).

[0079] The XRD test results of the hydrogen evolution cathode of this embodiment are as follows: Figure 2 As shown, there are obvious characteristic peaks of Ni-Mo-N compounds, Mo-N compounds, Mo-C compounds, Ni and graphite in the spectrum, indicating that the prepared cathode is composed of designed elements.

[0080] Example 2

[0081] The difference between this embodiment and embodiment 1 is that step (1) and step (3) are adjusted to:

[0082] (1) Prepare the materials according to the mass ratio of Ni powder: Mo powder: polyvinylidene fluoride: N-methylpyrrolidone = 45:45:10:115;

[0083] (3) Mix polyvinylidene fluoride and N-methylpyrrolidone and stir them thoroughly to form a binder glue solution.

[0084] The remaining steps and parameters are the same as those in Example 1.

[0085] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 6500-6600 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis.

[0086] Example 3

[0087] The difference between this embodiment and embodiment 1 is that step (1) and step (2) are adjusted to:

[0088] (1) Prepare the materials according to the mass ratio of NiSO4·6H2O:MoS2:polyvinylpyrrolidone:carboxymethyl cellulose:styrene-butadiene rubber (50% emulsion):deionized water = 130:50:1.5:1.5:2:120;

[0089] (2) NiSO4·6H2O and MoS2 were placed in a ball mill and ball milled at a speed of 280 rpm for 4 h.

[0090] The remaining steps and parameters are the same as those in Example 1.

[0091] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 7200-7350 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis.

[0092] Example 4

[0093] This embodiment provides a method for preparing a hydrogen evolution cathode, the method comprising:

[0094] (1) NiMoO4 was synthesized by a hydrothermal method. First, nickel nitrate (Ni(NO3)2·6H2O) and sodium molybdate (Na2MoO4·2H2O) were added to deionized water in a molar ratio of 1:1.5 and stirred evenly. The mass of deionized water was 40 times the sum of the mass of nickel nitrate and sodium molybdate. The mixed solution was then placed in a high-temperature and high-pressure stainless steel reactor lined with polytetrafluoroethylene for a hydrothermal reaction at a temperature of 125°C for 5 hours. After the reaction was completed and cooled to room temperature, NiMoO4, the active material precursor, was obtained.

[0095] (2) Prepare the materials according to the mass ratio of NiMoO4: nitrogen-containing phenolic resin: LA type water-based adhesive: deionized water = 95:1.5:3.5:120;

[0096] (3) NiMoO4, nitrogen-containing resin, LA-type water-based adhesive, and deionized water were mixed in proportion, heated at 60°C, and stirred to form a slurry;

[0097] (4) Use a brush to evenly coat the slurry on a 10cm*10cm twill nickel mesh. Then pre-dry at 80°C for 8 minutes.

[0098] (5) Roll the pre-dried sample with a roller press to compress the sample thickness to 75% of the original thickness;

[0099] (6) The pre-dried and rolled twill nickel mesh loaded with the slurry was placed in a reaction furnace and vacuumed. Argon gas was then introduced at a flow rate of 50 mL / min. The temperature was then increased at a heating rate of 8°C / min. When the temperature reached 460°C, ammonia gas was introduced at a flow rate of 30 mL / min. The mesh was sintered in an ammonia atmosphere for 90 min. After sintering, argon gas was introduced at a flow rate of 50 mL / min.

[0100] (7) After the temperature in the furnace drops to room temperature, a hydrogen evolution cathode is obtained.

[0101] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 7300-7500 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis.

[0102] Example 5

[0103] The difference between this embodiment and embodiment 1 is that step (7) is adjusted to "placing the pre-dried nickel foam loaded with the slurry in a reaction furnace, performing a vacuum treatment, and then introducing argon at a flow rate of 100 mL / min, and then heating at a heating rate of 6°C / min. When the temperature reaches 560°C, introducing ammonia at a flow rate of 60 mL / min, sintering in an ammonia atmosphere for 60 minutes, and introducing argon at a flow rate of 100 mL / min after the sintering is completed."

[0104] The remaining steps and parameters are the same as those in Example 1.

[0105] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 6560-6850 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis.

[0106] Example 6

[0107] The difference between this embodiment and embodiment 1 is that step (1) is adjusted to "prepare materials according to the mass ratio of Ni powder: Mo powder: polyvinyl pyrrolidone: carboxymethyl cellulose: styrene-butadiene rubber (50% emulsion): deionized water = 80:13.2:2.5:2:2.3:120".

[0108] The remaining steps and parameters are the same as those in Example 1.

[0109] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 6150-6200 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis.

[0110] Example 7

[0111] The difference between this embodiment and embodiment 1 is that step (1) is adjusted to "prepare materials according to the mass ratio of Ni powder: Mo powder: polyvinyl pyrrolidone: carboxymethyl cellulose: styrene-butadiene rubber (50% emulsion): deionized water = 16:78:1.5:1.5:3:120".

[0112] The remaining steps and parameters are the same as those in Example 1.

[0113] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 6200-6400 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis.

[0114] Example 8

[0115] The difference between this embodiment and embodiment 1 is that step (1) is adjusted to "prepare materials according to the mass ratio of Ni powder: Mo powder: polyvinyl pyrrolidone: carboxymethyl cellulose: styrene-butadiene rubber (50% emulsion): deionized water = 40:40:5:5:10:120".

[0116] The remaining steps and parameters are the same as those in Example 1.

[0117] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 6000-6100 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis.

[0118] Example 9

[0119] The difference between this embodiment and embodiment 1 is that ammonia gas is not introduced in step (7).

[0120] The remaining steps and parameters are the same as those in Example 1.

[0121] The hydrogen evolution cathode prepared in this example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 6500-6650 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of hydrogen electrolysis.

[0122] Example 10

[0123] The difference between this embodiment and embodiment 1 is that the ratio of polyvinyl pyrrolidone and carboxymethyl cellulose is increased to increase the slurry viscosity to 9000 mPa·s.

[0124] The remaining steps and parameters are the same as those in Example 1.

[0125] During the coating process of the slurry of this embodiment, some agglomeration occurred, and the loading distribution of the active material precursor was uneven. The hydrogen evolution cathode prepared in this embodiment was cut and placed in an alkaline water electrolysis hydrogen production electrolyzer with an effective size of 4cm*5cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85℃, and the single-chamber cell voltage was 2V. Under the above conditions, the current density was 6150-6250A / m 2 , lower than Example 1.

[0126] Example 11

[0127] The difference between this embodiment and embodiment 1 is that the ratio of polyvinyl pyrrolidone and carboxymethyl cellulose is reduced to reduce the slurry viscosity to 1000 mPa·s, so that the coating loading of the material on the nickel foam after pre-drying is 15 mg / cm 2 .

[0128] The remaining steps and parameters are the same as those in Example 1.

[0129] The preparation method of this embodiment will result in a smaller load of slurry coating. The hydrogen evolution cathode prepared in this embodiment is cut and placed in an alkaline water electrolysis hydrogen production electrolyzer with an effective size of 4cm*5cm. The electrolyte is 30% potassium hydroxide, the electrolysis temperature is 85℃, and the single-chamber cell voltage is 2V. Under the above conditions, the current density is 6100-6230A / m 2 , lower than Example 1.

[0130] Comparative Example 1

[0131] The difference between this comparative example and Example 1 is that in step (1), the mass of Mo powder is replaced by Ni powder, so that Ni powder: polyvinyl pyrrolidone: carboxymethyl cellulose: styrene-butadiene rubber (50% emulsion): deionized water = 95:1.5:1.5:2:120.

[0132] The remaining steps and parameters are the same as those in Example 1.

[0133] The hydrogen evolution cathode prepared in this comparative example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 4800-4950 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of electrolytic hydrogen production. Compared with Example 1, the current density is significantly reduced.

[0134] Comparative Example 2

[0135] The difference between this comparative example and Example 1 is that in step (1), the mass of Ni powder is replaced by Mo powder, so that Mo powder: polyvinyl pyrrolidone: carboxymethyl cellulose: styrene-butadiene rubber (50% emulsion): deionized water = 95:1.5:1.5:2:120.

[0136] The remaining steps and parameters are the same as those in Example 1.

[0137] The hydrogen evolution cathode prepared in this comparative example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 4250-4350 A / m 2 , and the current density remains basically stable over time, which shows that the hydrogen evolution cathode has the characteristics of high current density and high stability of electrolytic hydrogen production. Compared with Example 1, the current density is significantly reduced.

[0138] Comparative Example 3

[0139] This comparative example provides a method for preparing a hydrogen evolution cathode, the preparation method comprising:

[0140] (1) Prepare the materials according to the mass ratio of Ni powder: Mo powder = 50:45;

[0141] (2) Ni powder and Mo powder were placed in a ball mill and milled at a speed of 240 rpm for 2 h.

[0142] (3) The ball-milled powder was evenly spread on a 10 cm*10 cm nickel foam and rolled using a roller press to compress the sample to 75% of its original thickness;

[0143] (4) The rolled nickel foam was placed in a reactor and vacuumed, then argon was introduced at a flow rate of 50 mL / min, and then the temperature was increased at a rate of 8°C / min. When the temperature reached 460°C, ammonia was introduced at a flow rate of 30 mL / min, and the product was sintered in an ammonia atmosphere for 90 min. After the sintering was completed, argon was introduced at a flow rate of 50 mL / min.

[0144] (5) After the reaction is completed and the temperature in the furnace drops to room temperature, the prepared cathode is obtained.

[0145] The hydrogen evolution cathode prepared in this comparative example was cut and placed in an alkaline water electrolysis hydrogen production electrolytic cell with an effective size of 4 cm*5 cm. The electrolyte was 30% potassium hydroxide, the electrolysis temperature was 85°C, and the single-chamber cell voltage was 2V. Under the above conditions, the current density reached 4750-4850 A / m 2 , and the current density remained essentially stable over time, indicating that the hydrogen evolution cathode possesses the characteristics of high current density and high stability for hydrogen production by electrolysis. Compared to Example 1, the current density was significantly reduced. Furthermore, in this comparative example, the active material shed severely as the electrolysis progressed, resulting in poor stability.

[0146] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a hydrogen evolution cathode, characterized in that: The preparation method comprises: (1) mixing an active material precursor, a binder, and a solvent to obtain a slurry; (2) coating the slurry on the surface of a cathode substrate, and then sintering the slurry under a reducing atmosphere to obtain the hydrogen evolution cathode; The active material precursor includes a Ni source and a Mo source; and the binder includes C and N elements.

2. The preparation method according to claim 1, characterized in that The Ni source includes at least one of a Ni element, a Ni-containing alloy, and a Ni-containing compound; Preferably, the Ni-containing compound comprises a Ni salt, and the Ni salt comprises NiMoO4; Preferably, the Mo source includes at least one of a simple Mo substance, a Mo-containing alloy, and a Mo-containing compound; Preferably, the Mo-containing compound comprises a Mo salt, and the Mo salt comprises NiMoO4; Preferably, in the active material precursor, the molar ratio of Ni element to Mo element is 1:(0.1-3).

3. The preparation method according to claim 1 or 2, characterized in that The binder includes a first binder, which includes any one or a combination of at least two of polyvinyl pyrrolidone, a nitrogen-containing resin, or an LA-type water-based binder; Preferably, the binder further comprises a second binder, and the second binder comprises any one or a combination of at least two of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl alcohol, polymethacrylate or polyvinylidene fluoride; Preferably, the mass ratio of the binder to the active material precursor is 1:(4-100); Preferably, the solvent includes any one of water, ethanol, acetone or N-methylpyrrolidone, or a combination of at least two thereof.

4. The preparation method according to any one of claims 1 to 3, characterized in that The mixing in step (1) is stepwise mixing, and the stepwise mixing comprises the following steps: firstly mixing the binder and the solvent to obtain a binder glue solution, and then mixing the binder glue solution with the active material precursor; Preferably, the mass ratio of the binder to the solvent in the binder glue is 1:(1-100); Preferably, the viscosity of the slurry is 800 to 10000 mPa·s.

5. The preparation method according to any one of claims 1 to 4, characterized in that The cathode substrate comprises a nickel-based substrate, and the nickel-based substrate comprises any one or a combination of at least two of nickel foam, nickel alloy foam, nickel mesh, or nickel alloy mesh; Preferably, the coating method includes any one of scraping, brushing, spraying or slurrying, or a combination of at least two of them; Preferably, the total coating amount of the active material precursor and the binder is 10 to 500 mg / cm 2 .

6. The preparation method according to any one of claims 1 to 5, characterized in that Before the sintering, the coated product is pre-dried; Preferably, the pre-drying temperature is 40-95°C, and the pre-drying time is 3-30 minutes; Preferably, the heating rate of the sintering is 5 to 20°C / min; Preferably, the sintering temperature is 300-1000°C; Preferably, the sintering time is 20 to 1000 minutes.

7. The preparation method according to any one of claims 1 to 6, characterized in that The reducing gas in the reducing atmosphere includes ammonia; Preferably, the ammonia gas is introduced at a rate of 10 mL / min to 50 L / min.

8. The preparation method according to any one of claims 1 to 7, characterized in that The preparation method specifically comprises the following steps: (I) mixing a binder and a portion of a solvent to obtain a binder paste, and then mixing the binder paste, an active material precursor, and the remaining portion of the solvent to obtain a slurry; The active material precursor includes a Ni source and a Mo source; in the active material precursor, the molar ratio of Ni element to Mo element is 1:(0.1-3); the binder includes C element and N element; the mass ratio of the binder to the active material precursor is 1:(4-100); the mass ratio of the binder to the solvent in the binder glue is 1:(1-100); the viscosity of the slurry is 800-10000 mPa·s; (II) coating the slurry on the surface of a cathode substrate, and then pre-drying the slurry at 40-95° C. for 3-30 minutes, then placing the pre-dried product in a first atmosphere, heating it to 300-1000° C. at a heating rate of 5-20° C. / min, introducing a reducing gas, and sintering it in the reducing atmosphere for 20-1000 minutes. After sintering, placing it in a second atmosphere for cooling to obtain the hydrogen evolution cathode; The total coating amount of the active material precursor and the binder is 10 to 500 mg / cm 2 ; The reducing gas in the reducing atmosphere includes ammonia, and the introduction amount of the ammonia is 10mL / min~50L / min; the first atmosphere and the second atmosphere are both protective atmospheres, and the gases in the first atmosphere and the second atmosphere independently include argon and / or nitrogen, and the gas flow rates in the first atmosphere and the second atmosphere are independently 10mL / min~50L / min.

9. A hydrogen evolution cathode, characterized in that The hydrogen evolution cathode is prepared by the preparation method according to any one of claims 1 to 8; The hydrogen evolution cathode comprises a cathode substrate and an active material layer arranged on the surface of the cathode substrate; the active material in the active material layer comprises a NiMoN compound and a C coating layer coated on the surface of the NiMoN compound.

10. Use of the hydrogen evolution cathode according to claim 9, characterized in that: The hydrogen evolution cathode is applied in the field of hydrogen production by electrolysis of water.

Citation Information

Patent Citations

  • Nickel-molybdenum-iron hydrogen evolution electrode with ordered porous structure, preparation method and application

    CN114250485A